Electrochemical Performance of MnO2/Graphene Flower-like Microspheres Prepared by Thermally-Exfoliated Graphite - Liu, Xuyue; Liang, Bing; Hong, Xiaodong; Long, Jiapeng (Frontiers in Chemistry, 2022)
To enhance the electrochemical performance of MnO2/graphene composite, herein, thermally-exfoliated graphite (TE-G) is adopted as raw materials, and a hydrothermal reaction is conducted to achieve the exfoliation of TE-G and the loading of MnO2 nanosheets. Through optimizing the TE-G/KMnO4 ratio in the redox reaction between carbon and KMnO4, flower-like MnO2/G microspheres (MnO2/G-10) is obtained with 83.2% MnO2 and 16.8% residual graphene. Meanwhile, corresponding MnO2/rGO composites are prepared by using rGO as raw materials. Serving as a working electrode in three-electrode system, MnO2/G-10 composite displays a specific capacitance of 500 F g-1 at 1 A g-1, outstanding rate performance and a capacitance retention of 85.3% for 5000 cycles. The performance is much better than that of optimized MnO2/rGO composite. The reason is ascribed to that the high carbon fraction in TE-G results in a high fraction of MnO2 in composite, and the oxygen-containing groups in rGO reduces the resulting MnO2 fraction in composite. The superior electrochemical performance of MnO2/G-10 is dependent on hierarchical porous structure constructed by MnO2 nanosheet arrays and residual graphene layer in composite. In addition, a supercapacitor assembled by TE-G negative electrode and MnO2/G positive electrode also exhibits a superior performance. In consideration of the low cost of raw materials, the MnO2/G composite exhibits a great application potential in supercapacitors field.